PRINCIPLES OF SYSTEMATIC APPROACH TO MANAGING THE UPBRINGING OF YOUNG GENERATION - R. Gavva (Вестник университета)
Increasing the effectiveness of Russian educational and pedagogical complex is an urgent task. Without solving this task, it is difficult to solve the problem of weakening moral ideals by a part of Russian youth. Overcome the gap between education and upbringing is due to the use of system approach in the state, public, school, family management of educational processes in childhood and adolescence. The article outlines and substantiates the principles of the system approach, which must be strictly observed by the participants in the management of the upbringing of the younger Russian generation.